Cultural Acculturation of Yemeni Zapin Dance and Malay Dance in Malaysia As A Means of Islmic Teaching - Hafis Muzakir; Ahmad Jazuli (CMES (Center of Middle Eastern Studies), 2021)
This research was conducted to explain the cultural acculturation of the Yemeni and Malay zapin dance as a means of da'wah Islamiyah in Malaysia. The method used in this research is descriptive qualitative. In this research, literature study was also carried out as a data collection method. There is a theory in this research, namely the theory of cultural diffusion and from the point of view of a historical approach. The aim of this research is to reveal the acculturation elements of the Yemeni and Malay zapin dance. Then describe the Islamic da'wah function and the value between the two parties behind the zapin dance. The results that can be concluded from the acculturation of the Yemeni zapin dances and the Malay dances in Malaysia are producing all kinds of changes including the elements of dancers, musical instruments, movements, and the lyrics or songs used in these dances.